PENGARUH STORE ATMOSPHERE (SUASANA TOKO) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT.METRO ABADI SEMPURNA SEMESTA PEKANBARU - Ansori, Putra Budi; Lestari, Lidya (Eko dan Bisnis: Riau Economic and Business Review, 2017)
This research was conducted in the research conducted at PT. Metro Abadi Sempurna Semesta Pekanbaru in 2017. The aim of this study is to determine the influence store atmosphere on on purchase decisions custumers at PT. Metro Abadi Sempurna Semesta Pekanbaru in . Technique analysis data using descriptive analysis and quantitative. With the methods the sample collection of sampling convenience. It means respondents ( a subject ) selected by chance alone from members of the population who are willing to are only sampled, as many as 100 customers.Based on the results of a test of linear regression equation worship of idols with the equation regression Y = 15.814 + 0.437X . The regression coefficient are positive, means the better store atmosphere given, so the decisions is increased. T test results, the value of t_count for the variable store atmosphere as follows: has a value of t_count 6.614 > t_table of 1,984. So this means that the store atmosphere significant on variabels  purchase decisions custumers at PT. Metro Abadi Sempurna Semesta Pekanbaru Then to value  r _ square of  30.9 %  show their contribution given variable store atmosphere  on variables purchase decisions, while the rest of 69,1.% influenced by other variables that aren t pursuing in this research